Multiplicity of satellite DNA sequences in Drosophila melanogaster. - Lohe, A R (1986)
Three Drosophila melanogaster satellite DNAs (1.672, 1.686, and 1.705 g/ml in CsCl), each containing a simple sequence repeated in tandem, were cloned in pBR322 as small fragments about 500 base pairs long. This precaution minimized deletions, since inserts of the same size as the fragments used for cloning were recovered in a stable form. A homogeneous tandem array of one sequence type usually extended the length of the insert. Eleven distinct repeat sequences were discovered, but only one sequence was predominant in each satellite preparation. The remaining classes were minor in amount. The repeat unit lengths were restricted to 5, 7, or 10 base pairs, with sequences closely related. Each sequence conforms to the expression (RRN)m(RN)n, where R is A or G. The multiplicity of simple repeated sequences revealed despite the small sample size suggests that numerous repeat sequences reside in heterochromatin and that particular rules apply to the structure of the repeating sequence.